Triage and management of probable Covid-19 patients in the intensive care unit during the pandemic period (Annals of Medical Research, 2021)
Aim: Republic of Turkey Ministry of Health dedicated our hospital as a transplant center during the pandemic period. We admitted probable Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infection (COVID-19) cases and intensive care unit (ICU) patients from other centers, while confirmed COVID-19 cases were transferred to dedicated pandemic hospitals. The aim of this study was to determine the demographic parameters, clinical courses and outcomes of probable COVID-19 patients and to compare survivors with non-survivors admitted to our ICU.Materials and Methods: After Ethics Committee approval, 93 patients admitted to our ICU between March 23 and May 13 were analyzed retrospectively.Results: Mean age was 68.5y (60.2% male). Dyspnea (67.7%) was the most common symptom and hypertension (68.6%) was the most common comorbidity. None of PCR tests for SARS-CoV-2 were positive. Bilateral ground-glass (25.8%) and consolidation (14%) were the most common signs at chest computed tomography. Mean Acute Physiology and Chronic Health Evaluation System (APACHE II) score was 20.2 at ICU admission. Fifty-seven patients (61.3%) had pneumonia findings in lung X-ray or computerized tomography (CT). Thirty-four patients (36.6%) received low flow oxygen, six (9.7%) had high flow nasal oxygen and 27 (29%) had invasive mechanical ventilation. Forty patients (43%) had vasopressor therapy and 24 (25.8%) patients had renal replacement therapy due to acute kidney injury. Laboratory data including D-dimer, C-reactive protein, ferritin, creatinine kinase and procalcitonin were significantly higher in non-survivors when compared to survivors. The overall ICU mortality rate was 44.1%.Conclusions: A triage protocol of Turkish Study of Scientific Board based on clinical, laboratory and radiological findings for probable COVID-19 patients was applied in our center during the pandemic period. So, we ensured the effective usage of scarce ICU resources. The mortality rate of probable COVID-19 patients admitted to our ICU was found to be higher than the predicted mortality rate according to their APACHE-II score.
Keywords: Coronavirus; COVID-19; intensive care unit; SARS-CoV-2; triage